ANALISIS TERHADAP HAK PILIH TNI DAN POLRI DALAM PEMILIHAN UMUM - Setiajeng Kadarsih; Tedi Sudrajat (Faculty of Law, Universitas Jenderal Soedirman, 2011)
In this reformation era, there were discourses on the recovery of the right to vote for members of the Indonesian National Army (TNI) and Indonesian National Police (Polri) in the General Election. The willingness of those recovery based on the development of democratization and human rights, that places the right to vote as a fundamental right that cannot be infringed by the state. The problem that arises are how the arrangement of the right to vote for the TNI and Polri in the Indonesian General Election when it viewed from the perspective of the political history and how the legal synchronization between the right to vote for TNI and Polri when it viewed from the conception of human rights in the context of a democratic society in Indonesia. Based on the results, it known that there are setback in the arrangement of the right to vote for armed forces and police in three periods. In old order, armed forces and police were given the right to vote in the election. In the new order, the Armed Forces were not entitled to vote, but the presence of armed forces in the realm of regulated political sphere in particular through the lifting mechanism in the legislature. While in reformation era, the right to vote and vote for members of the military and police were removed, so the military and police only carry out the state tasks without any political rights inherent in that institution. This indicates that the legal arrangements concerning the right to vote according to the perspective of human rights in the context of a democratic society is not yet in sync with each other.